Estrogen receptor beta rs1271572 polymorphism and invasive ovarian carcinoma risk: Pooled analysis within the ovarian cancer association consortium - Lurie, Galina; Wilkens, Lynne R.; Thompson, Pamela J.; Shvetsov, Yurii B.; Matsuno, Rayna K.; Carney, Michael E.; Palmieri, Rachel T.; Wu, Anna H.; Pike, Malcolm C.; Pearce, Celeste L.; Menon, Usha; Gentry-Maharaj, Aleksandra; et al. (PLoS ONE, 2011)
The association of ovarian carcinoma risk with the polymorphism rs1271572 in the estrogen receptor beta (ESR2) gene was examined in 4946 women with primary invasive ovarian carcinoma and 6582 controls in a pooled analysis of ten case-control studies within the Ovarian Cancer Association Consortium (OCAC). All participants were non-Hispanic white women. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using unconditional logistic regression adjusted for site and age. Women with the TT genotype were at increased risk of ovarian carcinoma compared to carriers of the G allele (OR = 1.10; 95%; CI: 1.01-1.21; p = 0.04); the OR was 1.09 (CI: 0.99-1.20; p = 0.07) after excluding data from the center (Hawaii) that nominated this SNP for OCAC genotyping A stronger association of rs1271572 TT versus GT/GG with risk was observed among women aged ≤50 years versus older women (OR = 1.35; CI: 1.12-1.62; p = 0.002; p for interaction = 0.02) that remained statistically significant after excluding Hawaii data (OR = 1.34; CI: 1.11-1.61; p = 0.009). No heterogeneity of the association was observed by study, menopausal status, gravidity, parity, use of contraceptive or menopausal hormones, tumor histological type, or stage at diagnosis. This pooled analysis suggests that rs1271572 might influence the risk of ovarian cancer, in particular among younger women. © 2011 Lurie et al.
CRIS-Team Scopus Importer:2021-07-19